1997
DOI: 10.3141/1587-09
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Modal Emissions From Diverse In-Use Vehicle Fleet

Abstract: Research Program. This paper describes the initial phase of a longterm project with national implications for the improvement of transportation and air quality. The overall objective of the research is to develop and verify a comprehensive modal emissions model that accurately reflects the impacts of a vehicle's operating mode. The model is comprehensive in the sense that it will be able to predict emissions for a wide variety of light-duty vehicles (LDVs, i.e., cars and trucks) in various states of condition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 2 publications
1
30
0
Order By: Relevance
“…One distinct advantage of this physical approach is that it is possible to adjust many of these physical parameters to predict energy consumption and emissions of future vehicle models and applications of new technology (e.g., aftertreatment devices). Further information on the CMEM effort may be found elsewhere (4,(7)(8)(9).…”
Section: Matthew Barth and Kanok Boriboonsomsin 163mentioning
confidence: 99%
“…One distinct advantage of this physical approach is that it is possible to adjust many of these physical parameters to predict energy consumption and emissions of future vehicle models and applications of new technology (e.g., aftertreatment devices). Further information on the CMEM effort may be found elsewhere (4,(7)(8)(9).…”
Section: Matthew Barth and Kanok Boriboonsomsin 163mentioning
confidence: 99%
“…The associated effects of these factors on emissions and fuel consumption have been discussed elsewhere. 6,8,24 From the traffic model interface perspective, the number of input variables for the emission prediction is critical. There has to be a compromise between the accuracy and detail of a model and the easy applicability of the model.…”
Section: The Trip-based Resultsmentioning
confidence: 99%
“…Inspection/maintenance program smog-check inspections provide data on in-use vehicles, but are inadequate indicators of on-road emissions since the tests are performed over only two no-load engine operating conditions (2500 rpm and idle). While more recent research has focused on correlating driving mode with emissions (Hansen et al, 1995;Jensen, 1995;Joumard et al, 1995;Sjodin and Lenner, 1995;Barth et al, 1997;Washington et al, 1997;Young et al, 1997), emissions were usually estimated from emission models rather than measured directly in the ®eld. The few studies that have used on-board gas analyzers (Schurmann and Staab, 1990;Kelly and Groblicki, 1993;Guenther et al, 1996) demonstrated the capabilities of these instruments to measure second-by-second emission levels to aid in repair of malfunctioning emission systems, but made no e ort to correlate driving style and emission levels.…”
Section: Quantifying Real-world Automobile Emissionsmentioning
confidence: 99%
“…Denis et al, 1994;Ross et al, 1995). New driving cycles are currently being proposed since it has recently become apparent that the FTP cycle is too limited to account for today's real-world driver behavior (Ross et al, 1995;Barth et al, 1997;Washington et al, 1997), but adoption of a new cycle awaits widespread ®eld data collection and analysis. Key to adoption of a new cycle is demonstration that it adequately represents today's real-world driving.…”
Section: Driver Variability And`o -Cycle' Emissionsmentioning
confidence: 99%